Analisis Pengaruh Obesitas pada Derajat Keparahan Pasien Covid-19 Gelombang ke-2 yang Dirawat Inap di RSUD Dr. Saiful Anwar Malang - Cendani, Wulan; Djajalakasana, Susanthy; Santosa, I; Djajalaksana, Susanthy (RSUD Dr. Saiful Anwar Province of East Java, 2024)
Background : Based on WHO data, Covid-19 has officially been declared a pandemic because its spread has reached more than 100 infected countries. Several risk factors can affect the severity of Covid-19 patients, one of which is comorbid obesity. The Covid-19 pandemic occurred when the prevalence of overweight/obesity was increasing in almost every country in the world. Chronic inflammation associated with obesity, impaired immune function, and increased expression of ACE 2 contribute to disease severity and worsen clinical outcomes in obese patients with Covid-19 infection. Aim : This study aims to analyse the effect of obesity on the severity of the second wave of Covid-19 patients who were hospitalized at RSUD dr. Saiful Anwar Malang. Methods : This research is an analytic observational study with cross sectional approach. The sample consisted of 46 Covid-19 patients with obesity who were hospitalized at RSUD dr. Saiful Anwar Malng. The data acquired will be analysed using Mann Whitney non-parametric analysis test. Results : In the obese and non-pbese groups, the p-value was 0,042 and the odds ratio was 1,23. In the distribution of age and sex groups, each group obtained a p-value of 0,363 and 0,592. Conclusion : There is a significant difference in obesity among patients, with a 1,23-fold increased risk of experiencing severity compared to those who are not obese. Meanwhile, for the distribution based on age and sex, there was no significant difference, but it tended to have a more critical degree of severity towards men and older age.